2015
DOI: 10.1111/resp.12572
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity and asthma management among adults presenting to the emergency department

Abstract: We investigated whether racial/ethnic disparities exist in asthma management among 1785 adults requiring emergency department (ED) treatment. In this multicentre study, non-Hispanic blacks with increased chronic asthma severity were only as likely (P > 0.05) as non-Hispanic whites or Hispanics to utilize controller medications or see asthma specialists before ED presentation and to be prescribed recommended inhaled corticosteroids at ED discharge. Improved ED education on evidence-based chronic disease managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…6 The study setting, methods of measurement, and collected variables have been reported previously. 7 13 Briefly, we recruited EDs by inviting sites that had participated in the earlier MARC study that evaluated ED patients with asthma exacerbation during 1996 to 2001. 5 , 14 , 15 A total of 48 EDs across 23 U.S. states completed the current study.…”
Section: Methodsmentioning
confidence: 99%
“…6 The study setting, methods of measurement, and collected variables have been reported previously. 7 13 Briefly, we recruited EDs by inviting sites that had participated in the earlier MARC study that evaluated ED patients with asthma exacerbation during 1996 to 2001. 5 , 14 , 15 A total of 48 EDs across 23 U.S. states completed the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Involving patients in this process may help, and a questionnaire used to identify asthma in early childhood developed in conjunction with parents shows promise in this regard . In addition, engagement with treatment may be dependent on socio‐economic and ethnic factors (rather than simply ethnic background), leading to worse asthma in different ethnic groups not being addressed . Although many socio‐economic factors cannot be altered, obesity is a modifiable ‘lifestyle’ disease, and the influence of obesity on respiratory illness, or bariatric pulmonology is a growth area with significant pulmonary health gains possible if weight loss can be achieved.…”
Section: Asthmamentioning
confidence: 99%
“…4 In addition, engagement with treatment may be dependent on socio-economic and ethnic factors (rather than simply ethnic background), leading to worse asthma in different ethnic groups not being addressed. 6 Although many socio-economic factors cannot be altered, obesity is a modifiable 'lifestyle' disease, and the influence of obesity on respiratory illness, or bariatric pulmonology is a growth area with significant pulmonary health gains possible if weight loss can be achieved. Asthma in the obese is a complex problem with obesity promoting a pro-inflammatory process 7 ; however, evidence of weight loss was published in Respirology following diet and exercise.…”
mentioning
confidence: 99%
“…Similarly, Black individuals are more likely to live in areas with greater exposure to hazards such as air pollution, which might increase the prevalence and severity of chronic diseases. 37 38 These differences in neighborhood and home environments and in resources could make it more challenging for Black patients to recover at home and to attend postoperative clinical visits. 39 Our finding that surgical mortality is higher among Black men compared with other subgroups of race and sex is consistent with the finding that Black men have substantially shorter life expectancy at birth compared with other subgroups.…”
Section: Discussionmentioning
confidence: 99%